Open Depressed and Compound Elevated Skull Fracture over the Superior Sagittal Sinus: A Case Report - Andi Nugraha Sendjaja; Agung Budi Sutiono; Ahmad Faried; Muhammad Zafrullah Arifin (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
This is a case report of an open depressed and compound elevated skull fracture that located in the area where superior sagittal sinus lies beneath. This is a very rare variant of skull fractures. This patient was admitted to our Department of Neurosurgery Hasan Sadikin Hospital, Bandung Indonesia. He is a 14 years old male with motor vehicle accident and diagnosed with compound elevated and depressed skull fracture. A CT Scan demonstrated an Epidural hematoma with suggested cerebral prolapse. The initial GCS was 15 with slight hemiparesis and the patient underwent an emergency surgery. The elevated skull compound was fixated by a titanium mesh but we left the prolapse untouched, then the procedure followed by duraplasty using a pericranial flap. After 7 days of post-op treatment he was discharged without any neurological deficit. With proper emergency surgery, and by preserving the prolapsed brain tissue with fixation on the elevated skull fracture to prevent further injury may give a good results on this patient.